2018
DOI: 10.1038/s41598-018-26623-x
|View full text |Cite|
|
Sign up to set email alerts
|

A broad genomic panel of microsatellite loci from Brycon orbignyanus (Characiformes: Bryconidae) an endangered migratory Neotropical fish

Abstract: A broad panel of tens of thousands of microsatellite loci is unveiled for an endangered piracema (i.e. migratory) South American fish, Brycon orbignyanus. Once one of the main fisheries resources in the Platine Basin, it is now almost extinct in nature and focus of intense aquaculture activity. A total of 178.2 million paired-end reads (90 bases long) were obtained through the use of sequencing-by-synthesis (from a primary genomic library of 500 bp DNA fragments) and is made available through NCBI’s Sequence R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…In this study, we identified a total of 95,098 microsatellites based on sequences of the complete genome of A. gigas, a value close to that found for Monopterus albus (99,293) [32] and much larger than what was found for Brycon orbignyanus (81,241) [31]. These differences probably are due to the size of the databases, search criteria and bioinformatics tools used to identify the microsatellites [35].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In this study, we identified a total of 95,098 microsatellites based on sequences of the complete genome of A. gigas, a value close to that found for Monopterus albus (99,293) [32] and much larger than what was found for Brycon orbignyanus (81,241) [31]. These differences probably are due to the size of the databases, search criteria and bioinformatics tools used to identify the microsatellites [35].…”
Section: Discussionsupporting
confidence: 67%
“…The rapid development of sequencing technologies allowed the obtention of complete genome sequences from an increasing number of species [30], which is an excellent source for identification of microsatellite markers already used in several species [30,31,32,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid development of sequencing technologies allowed the obtention of complete genome sequences from an increasing number of species [ 33 ], which is an excellent source for identification of microsatellite markers already used in several species [ 34 38 ]. However, the use of sequencing Technologies demands laboratories equipped with high infrastructure and skilled personal resources, which in many cases does not match the reality of several laboratories in the Amazon region.…”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez-Rodriguez et al, 2010;Lopera-Barrero et al, 2010, 2014Ashikaga et al, 2015;Carmo et al, 2015;Castro et al, 2017). This yields a restricted number of usable loci and can lead to increasing artefactual noise in the analyses (Carmo et al, 2015).With the unveiling of the first 29 microsatellite loci from B. orbignyanus (Arias et al, 2016), by the application of next-generation sequencing (NGS) pipelines (Yazbeck et al, 2018), more reliable genetic analysis systems for this species can now be developed, in order to accelerate the profiling of extant and cultivated stocks in this threatened species. Recently, seven polymorphic microsatellite loci were also developed by means of traditional cloning methods, involving a microsatellite-enriched library prepared with hybridization capture process, and their transferability assayed, along five other new markers, in Brycon gouldingi and B. falcatus (Souza et al, 2018).…”
mentioning
confidence: 99%